Experimental comparison of grating- and propagation-based hard X-ray phase tomography of soft tissue - Lang, S.; Zanette, I.; Dominietto, M.; Langer, Max; Rack, A.; Schulz, Georg; Le Duc, G.; David, C.; Mohr, J.; Pfeiffer, F.; Mueller, B.; Weitkamp, Timm (Journal of Applied Physics, 2014)
When imaging soft tissues with hard X-rays, phase contrast is often preferred over conventional attenuation contrast due its superior sensitivity. However, it is unclear which of the numerous phase tomography methods yields the optimized results at given experimental conditions. Therefore, we quantitatively compared the three phase tomography methods implemented at the beamline ID19 of the European Synchrotron Radiation Facility: X-ray grating interferometry (XGI), and propagation-based phase tomography, i.e., single-distance phase retrieval (SDPR) and holotomography (HT), using cancerous tissue from a mouse model and an entire heart of a rat. We show that for both specimens, the spatial resolution derived from the characteristic morphological features is about a factor of two better for HT and SDPR compared to XGI, whereas the XGI data generally exhibit much better contrast-to-noise ratios for the anatomical features. Moreover, XGI excels in fidelity of the density measurements, and is also more robust against low-frequency artifacts than HT, but it might suffer from phase-wrapping artifacts. Thus, we can regard the three phase tomography methods discussed as complementary. The application will decide which spatial and density resolutions are desired, for the imaging task and dose requirements, and, in addition, the applicant must choose between the complexity of the experimental setup and the one of data processing.
CRIS-Team Scopus Importer:2023-03-08